A comprehensive book on selected questions and answers in electrical engineering - Rajput, R.K (S. Chand & Company Pvt. Ltd., 2014)
A comprehensive book on selected questions and answers in electrical engineering / Rajput, R.K. -- New Delhi: S. Chand & Company Pvt. Ltd., 2014 621.3076 R161 No. of Copies : 1